2017
DOI: 10.1177/1940161217723152
|View full text |Cite
|
Sign up to set email alerts
|

The Engaging Effect of Exemplars: How an Emotional Reaction to (Dis)Similar People in the News Media Affects Political Participation

Abstract: Journalists use ordinary people as exemplars in their news stories to make their reports more interesting and understandable for the audience. This journalistic practice has often been discussed as a potential democratic problem because of its effects on perceptions of and attitudes toward political issues. Taking exemplification theory as our starting point and drawing on research from decision-making and social psychology literature, we add to this discussion by examining how exemplars in news reports affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Thus, it is especially episodic framing that may function as a counterweight to the increasingly dominant neoliberal discourse of elite policymakers who put blame on individual citizens rather than on system failure (Guetzkow 2010), whereas thematic framing on itself does not affect attributions of individual responsibility. A decreasing attribution of responsibility to individual citizens as the outcome of more exposure to episodic framing aligns with the conclusions of previous experiments in the North-European context (Aarøe 2011;Andersen et al 2017;Boukes et al 2015). However, it conflicts with U.S.-based studies and Iyengar's (1991) prediction that episodic framing restricts citizens' ability to place public issues in a more general or abstract context and, therefore, would make the individual a more likely target for responsibility attributions.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it is especially episodic framing that may function as a counterweight to the increasingly dominant neoliberal discourse of elite policymakers who put blame on individual citizens rather than on system failure (Guetzkow 2010), whereas thematic framing on itself does not affect attributions of individual responsibility. A decreasing attribution of responsibility to individual citizens as the outcome of more exposure to episodic framing aligns with the conclusions of previous experiments in the North-European context (Aarøe 2011;Andersen et al 2017;Boukes et al 2015). However, it conflicts with U.S.-based studies and Iyengar's (1991) prediction that episodic framing restricts citizens' ability to place public issues in a more general or abstract context and, therefore, would make the individual a more likely target for responsibility attributions.…”
Section: Discussionsupporting
confidence: 89%
“…Social media has also been identified as the antecedent to PK apart from political participation. It has a positive relationship with knowledge levels by helping youth on seeking information on political activities (Adamu & Mohamad, 2019;Andersen et al, 2017;Gottfried et al, 2017;Ohme, 2020;Schafer, 2020;Weeks et al, 2017). The association between PK and media consumption also is found in online platforms (Lee & Xenos, 2019) which suggests the feasibility of this relationship on the social channels.…”
Section: Social Media Usagementioning
confidence: 92%
“…On the other hand, more recent studies within exemplar theory have demonstrated that human-interest stories actually might increase attribution of responsibility to government and support for political intervention (Boukes et al, 2015; Ostfeld and Mutz, 2014), particularly when the individuals featured are similar to the audience (Andersen et al, 2017); are portrayed as deserving and innocent (Hopmann et al, 2017) and when the story resonates with deep-seated values and prior beliefs (Chong and Druckman, 2007). As revealed by experiments, who is chosen to represent or illustrate an issue impacts how it is understood and where blame is directed.…”
Section: Analytical Frameworkmentioning
confidence: 99%